A study about cell activity on anodized Ti-6Al-4V by means of pulsed current - Vasconcellos, Luana M. R. [UNESP]; Villaça-Carvalho, Maria F. L. [UNESP]; Prado, Renata F. [UNESP]; Santos, Evelyn L. S. L. [UNESP]; Regone, Natal N. [UNESP]; Pereira, Marinalda C. [UNESP]; Codaro, Eduardo N. [UNESP]; Acciari, Heloisa A. [UNESP] (Taylors Univ Sdn Bhd, 2017)
Titanium and some of its alloys exhibit excellent anti-corrosive and biocompatibility properties due to rapid formation of a passive film on their surfaces when exposed to the atmosphere. However, such materials present poor osteoindutive properties. Surfaces modified via anodization are being proposed in this study to promote a chemical interaction between implants and bone cells. For this purpose, samples in Ti-6Al-4V alloy discs were anodized in a phosphoric acid solution using pulsed current for being applied in orthopaedic implants. The pulsed current is based on duty cycle (DC), which was supplied by a square wave pulse rectifier at 100 Hz and maximum tension of 30 V. A scanning electron microscope was used to obtain images of the anodized surfaces, thus revealing the presence of uniformly distributed pores over the entire surface, measuring approximately 2 mu m in diameter. Osteogenic cells grown on the surface of the control and anodized samples were assayed for cytotoxicity and mineralized matrix formation. The anodized surfaces presented a higher rate of viable cells after 10 days, as well as a higher amount of nodules (p = 0.05). In conclusion, these results suggest that the nanotopography promoted by anodization using pulsed current induces beneficial modulatory effects on osteoblastic cells.
Keywords: Anodizing; Osseointegration; Osteoblast activity; Ti-6Al-4V alloy